2003
DOI: 10.1177/0165551503296009
|View full text |Cite
|
Sign up to set email alerts
|

Do Impact Factors change with a change of medium? A comparison of Impact Factors when publication is by paper and through parallel publishing

Abstract: This paper reports the results of a bibliometric analysis of scholarly journals in the field of psychology. The Impact Factors of a sample of journals have been collected from Journal Citation Reports (JCR) provided by ISI. Changes in the Impact Factors were monitored annually over two periods, 1994–1995 and 2000–2001, the years before and after electronic journals appeared. The collected Impact Factors of scholarly journals from these two periods are compared in the available media. As a result, it is found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 8 publications
(9 reference statements)
1
18
0
Order By: Relevance
“…We sought to determine the half‐life of Web citations in a set of three leading and widely available IS journals ( IP&M , JASIST , and JDoc ) as well as investigate characteristics of links that might be associated with link decay. Shin (2003) found that the impact factor of journals increased when they became available in electronic formats. This suggests that the popularity of Web citations will not wane any time soon and that there are incentives to make scholarly material available online.…”
Section: Resultsmentioning
confidence: 99%
“…We sought to determine the half‐life of Web citations in a set of three leading and widely available IS journals ( IP&M , JASIST , and JDoc ) as well as investigate characteristics of links that might be associated with link decay. Shin (2003) found that the impact factor of journals increased when they became available in electronic formats. This suggests that the popularity of Web citations will not wane any time soon and that there are incentives to make scholarly material available online.…”
Section: Resultsmentioning
confidence: 99%
“…The next natural step was been to seek evidence for the impact of OA publishing using existing bibliometric techniques [as described in 4] and researchers showed that online availability of articles was associated with higher citation counts in several subject areas [18,19,20,21,22]. The increasing number of OA journals indexed in the Institute for Scientific Information (ISI) citation databases * , not only indicates their acceptance as a valid outlet for publishing scientific papers, but also encouraged researchers to use ISI citations as a measure of assessment [23] or to compare OA and non-OA journals impact across many disciplines [24].…”
Section: Introductionmentioning
confidence: 99%
“…• the investigation the impact of OA and non-OA journals (26-36); • the comparison of the citation rates before and after journal articles are made openly available (34,37-41); • the comparison of the journal's impact factor between OA and subscription journals (16,34,(42)(43)(44)(45)(46)(47)(48)(49)(50).…”
Section: Studies On the Investigations Of The Citation Performance Ofmentioning
confidence: 99%